Oddziaływanie kapitału zagranicznego na wzrost gospodarczy krajów członkowskich Unii Europejskiej - Stawicka, Magdalena Kinga (The Influence of Foreign Capital on the Economic Growth in the Member's of European Unions, 2008)
The main aim of this article is to show to the position and the meaning of foreign direct investment in the European Unions countries, and the influence of this on the basic macroeconomic index, which is real Gross Domestic Product. The article paid special attention to the fact that between inflow of foreign direct investment and real GDP in percentage appear to have a strong relationship. To examing this relativeness used the following statistical methods, as: Pearson's correlation and Regression analysis.(original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 19, s. 178-186